Pengungkapan Tanggung Jawab Sosial Memoderasi Pengaruh Profitabilitas dan Ukuran Perusahaan pada Nilai Perusahaan - Puspita Dewi, Ni Kadek Dona; Mertha, I Made (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p19, 2018)
This study is aimed to find empirical evidence concerning the effect of profitability and company size on the company value in which social responsibility disclosure is used as the moderating variables. This study was conducted on the food and beverage companies which were listed in Indonesian Stock Exchange during 2013-2016 periods. There are 11 companies used as the sample by using purposive sampling method. Non-participantmethod was used as the method of collecting data while Moderated Regression Analysis technique was used as the technique of analyzing data. Based on the analysis, it was found that both profitability and company size brought positive effect on the company value. Social responsibility disclosure weakened the effect of profitability on the company value. Meanwhile, it strengthened the effect caused by the company size. Keywords: Profitability, company size, social responsibility disclosure, company value